Effect of 2D perovskite layer and multivalent defect on the performance of 3D/2D bilayered perovskite solar cells through computational simulation studies. (15th July 2021) - Kumar, Anjan; Singh, Sangeeta; Mohammed, Mustafa K.A.; Esmail Shalan, Ahmed
Graphical abstract: Highlights: For market PSC, long-term reliability under open-air conditions is essential. (2D) perovskites seem to exhibit good stability due to the presence of hydrophobic organic spacers. Mixed perovskites is promising candidate for long-term stability and high performances. Using optical simulation features of SCAPS, absorption of light is computed in the proposed device. The computational results confirm the thickness effect of 2D perovskite on solar cell parameters. Abstract: Three-dimensional (3D) metal halide perovskite solar cells (PSCs) have a power conversion efficiency that is now comparable with conventional silicon solar cells. For PSC applications to succeed in the market, long-term reliability under open-air conditions is essential. Recent experiments have shown that two-dimensional (2D) perovskites seem to exhibit good stability due to the presence of hydrophobic organic spacers, but 2D PSCs are incapable of generating and transporting a large amount of charge due to their extended optical bandgaps. Mixed dimensional perovskites with dimension lies between 2D and 3D recently became a promising candidate to sustain long-term stability and high performances concurrently to address this obstacle. The current research article presents the finding of simulation-based studies performed on novel device architecture consisting of ITO/Nb-Ti2 O3 /3D Perovskite/2D Perovskite/Spiro-OMeTAD/Au. Using optical simulation features of SCAPS, absorption of light is computed in the proposed device. The computational results show that the thickness of the 2D perovskite layer badly affects the solar cell parameters. A thin 2D perovskite behaves as a capped coating that avoids the deterioration of 3D perovskite in open-air environments. The effect of a multivalent defect in the 3D perovskite layer is mathematically modelled, and their impact on overall performance parameters are analyzed. The findings are compared to the same configuration results, except where the absorber layer's multivalent defect has been substituted by a neutral defect of the same defect density of about (10 11 cm −3 ). Results show that the multivalent defect leads to an underestimation of the efficiency by 4.2%.